Hepatitis C Virus Infection in Children and Pregnant Women: An Updated Review of the Literature on Screening and Treatments - Ragusa, Rosalia; Corsaro, Liberato Simone; Frazzetto, Evelise; Bertino, Emanuele; Bellia, Maria Alessandra; Bertino, Gaetano (American Journal of Perinatology Reports, 2020)
Objective The aim of the paper is to review the current information relating to the diagnosis and treatment of hepatitis C virus (HCV) infection in pregnant women and children, particularly those infected by mother-to-child transmission.Study Design A review of published literature was performed to identify relevant articles published between January 2015 and March 2019 on: HCV infection in pregnant woman, mother-to child-transmission of HCV and HCV infection in pediatrics. The results of the evaluation of the different studies were summarized in two sections describing separately the screening and effective treatments in pregnant women and children.Results The rate of mother-to-child transmission of HCV is approximately 5%. HCV infection is strongly associated with cholestasis and preterm birth. Prenatal diagnosis of hepatitis C virus has a dual benefit for mother and child. Perinatally infected children develop cirrhosis in earlier age than those who acquire HCV as adolescents. Pregnant women with cirrhosis have a higher risk of poor maternal and neonatal outcomes than those without cirrhosis.Conclusion To improve public health, universal screening of pregnant women for HCV infection should be performed. Early identification of women and children with HCV infection is important to enable them to be included in assessment and/or treatment programs.
Keywords: HCV infection; mother-to-child transmission; HCV screening; direct-acting antivirals; pregnant women; perinatal outcome; pregnancy outcome